2003
DOI: 10.1038/nm960
|View full text |Cite|
|
Sign up to set email alerts
|

Dendritic cell–induced autoimmune heart failure requires cooperation between adaptive and innate immunity

Abstract: Genetic susceptibility and autoimmunity triggered by microbial infections are factors implicated in the pathogenesis of dilated cardiomyopathy, the most common cause of heart failure in young patients. Here we show that dendritic cells (DCs) loaded with a heart-specific self peptide induce CD4+ T-cell-mediated myocarditis in nontransgenic mice. Toll-like receptor (TLR) stimulation, in concert with CD40 triggering of self peptide-loaded dendritic cells, was shown to be required for disease induction. After reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
299
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(311 citation statements)
references
References 39 publications
9
299
1
2
Order By: Relevance
“…For example, the severe systemic disorder of septic shock caused by an extensive release of LPS in gram-negative infection could serve as potential indication for agents that dampen the TLR-mediated pro-inflammatory response. In the experimental setting of dilated autoimmune cardiomyopathy, Eriksson et al [2] demonstrated that induction of autoimmunity requires autoantigen presentation, CD40 costimulation and TLR activation, as TLR4-deficient mice fail to develop autoimmune heart disease in an endotoxin environment. We propose that the mechanism underlying the protective role of 1,25(OH) 2 D3 in Th1-mediated autoimmune disease involves down-regulation of antigen-presenting molecules, costimulatory CD40 and, most importantly, downregulation of TLR on APC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the severe systemic disorder of septic shock caused by an extensive release of LPS in gram-negative infection could serve as potential indication for agents that dampen the TLR-mediated pro-inflammatory response. In the experimental setting of dilated autoimmune cardiomyopathy, Eriksson et al [2] demonstrated that induction of autoimmunity requires autoantigen presentation, CD40 costimulation and TLR activation, as TLR4-deficient mice fail to develop autoimmune heart disease in an endotoxin environment. We propose that the mechanism underlying the protective role of 1,25(OH) 2 D3 in Th1-mediated autoimmune disease involves down-regulation of antigen-presenting molecules, costimulatory CD40 and, most importantly, downregulation of TLR on APC.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptors (TLR) are innate immune pattern recognition receptors that enable vertebrates to deal quickly and efficiently with invading foreign microorganisms such as bacteria, virus or fungi [1,2]. At present, ten human germ-line-encoded members of the TLR family have been identified [3].…”
Section: Introductionmentioning
confidence: 99%
“…For DC immunization, bone marrow-derived DCs (BMDCs) were generated as described (26). BMDCs were pulsed overnight with 10 mg/ml MyHC-a peptide and stimulated for another 4 h with 0.1 mg/ml LPS (Sigma-Aldrich) and 5 mg/ml anti-CD40 (BD Pharmingen) (15). Recipient mice received 2.5 3 10 5 pulsed and activated BMDCs i.p.…”
Section: Immunization Protocolsmentioning
confidence: 99%
“…EAM is a CD4 + T cell-mediated disease (7,14), and activation of self-Ag-loaded dendritic cells (DCs) is critical for expansion of autoreactive CD4 + T cells. Activation of TLRs and IL-1 type 1 receptor and their common downstream signaling adaptor molecule, MyD88, in self-Ag-presenting DCs is also critical for the development of EAM (11,15,16). Compared with inhibition of a single cytokine, a more effective treatment might be inhibition of various signaling pathways to induce production of cytokines through both innate and adaptive immunity.…”
mentioning
confidence: 99%
“…34,35 A recent study directly demonstrated that cardiac antigen-loaded dendritic cells (DCs) induced autoimmune myocarditis when they were activated and transferred. 36 Taken together, these studies suggest that EAM induction is closely associated with not only the myocarditic epitopes of cardiac myosin and their reactive T cells, but also with the activation of antigen-presenting cells (APCs) such as DCs by inflammatory cytokines. …”
mentioning
confidence: 91%